Analisis Model Kepemimpinan Karismatik dan Visioner - Adnan Adnan; Agus Gunawan; Encep Syarifudin (Tarbiatuna: Journal of Islamic Education Studies, 2024)
There are many leadership styles that can be applied in organizations, such as charismatic leadership and visionary leadership. Charismatic leaders emphasize ideological goals that link the group's mission to deep-rooted values, ideals, and aspirations shared by followers. Besides that, charismatic leadership is also based on the extraordinary power possessed by a person as a person. Visionary leadership brings about change within ourselves and includes the people involved in and or the entire organization to achieve higher levels of performance. This article demonstrates an alternative framework for implementing charismatic leadership in organizations that can improve employee outcomes (competencies-skills). Keywords: charismatic leadership, visionary leadership, organizational, charismatic leadership, visionary leadership